Вопросы построения компьютеризованных систем с элементами профессионального интеллекта - Павлов, В. В.; Шепетуха, Ю. М. (Видавництво Львівської політехніки, 2011)
Approach to development of computerized systems with the elements of artificial intelligence is examined. Issues of knowledge elicitation and deployment are discussed. As an example, man-machine system to provide safe ship maneuvering in complex conditions is considered.
Keywords: комп’ютеризована система; професійний інтелект; людино-машинний діалог; управління знаннями; попередження зіткнень суден